Proposed new showroom design for TRD at Lot 8248, Jalan 222, Petaling Jaya 47300 Selangor / Abdullah Harith Shamsuddin - Shamsuddin, Abdullah Harith (Faculty of Architecture, Planning and Surveying, UiTM Perak, 2008)
The final project of interior design for diploma is the manifestation to students’ understanding on process aspects of interior design that has been studied from the basic to presentation level of design proposal. The chosen product for this project is TRD showroom at Lot 8248, Jin 222, Petaling Jaya. The purpose of this project is to introduce various ranges of TRD products, deeply; and much important is to give service in upgrading sen/ice for Toyota. In running this project, the most important of the showroom is to make variety of design especially for TRD products. Plus, it is also to instill interest of people to motorsports arena. The research method for \ rQn this project is based on observation of showrooms and accessories shop through differences of local and international. The advantages that can be seen in this project, is to brighten up the world of motorsports to community of all walks of life as to eliminate the idea of unhealthyness of this arena. In conclusion, the new showroom design that will be run should have the characteristics and customers’ needs besides the suitable concept to be shown. The design hopefully, will give benefits to all, either local or foreigner generally and to Toyota users specifically